Early marriage of Madurese women: A case study - Yudho Bawono (INSPIRA: Indonesian Journal of Psychological Research, 2023)
Early marriage in Indonesia has become an issue that has attracted the attention of various child and women’s monitoring institution since the proposed of revisions to the Marriage Law No. 1 of 1974 specifically in increasing the age limit for women’s marriages from 16 years to 18 years. The effort to submit a revision to the law itself are based on various problems caused by the existence of early marriage. However, in contrast to the conditions in Madura, early marriage does not always cause problems such as these findings. Madurese women who marry early can also achieve happiness and harmony in their marriage. This study aims to describe Madurese women who married early using a qualitative method with a case study approach. Research participants are Madurese women who are married under the age of 18, live in Madura and are willing to be involved in the research. Data collection using interviews and field notes. The data analysis technique uses the Miles & Huberman interactive model by starting with data collection, data reduction, data display, verification or drawing conclusions. In checking the validity of the data uses triangulation and member check. Our findings reveal that early marriage was initially perceived by the participants as an unpleasant, but over time, early marriage has become a good thing for their lives.